ENHANCING CREATIVE MSME PERFORMANCE THROUGH BUSINESS INTELLIGENCE, NETWORK LEARNING, AND INNOVATION: EVIDENCE FROM JAKARTA - Nur Fitri Rahmawati; Citra Agnestia; Sukirno Sukirno; Felomino Gargar (Jurnal Apresiasi Ekonomi, 2026)
This study aims to analyse the effect of Business Intelligence and network learning on innovation and, in turn, on the performance of creative MSMEs in Jakarta. Grounded in the Resource-Based View and Knowledge-Based View, the study positions Business Intelligence and network learning as knowledge-based capabilities that drive innovation and performance. Data were collected through a survey of 400 owners/managers of creative MSMEs and analysed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that both Business Intelligence and network learning have positive and significant effects on innovation, with the effect of Business Intelligence being stronger than that of network learning. Innovation is found to have a positive and very strong effect on MSME performance. Mediation analysis further indicates that the effects of Business Intelligence and network learning on MSME performance are fully mediated by innovation. These findings highlight the importance of systematic business information management and network-based learning in fostering innovation as the main engine of performance improvement in creative MSMEs and offer implications for designing support programmes and simple Business Intelligence applications tailored to MSMEs. Keywords: Business Intelligence; Network Learning; Innovation; MSME Performance; Creative Msmes; Knowledge-Based View.